The University as a Means for Value Creation. Service-learning for Service Orientation - María A. Ramón-Jerónimo; Rosario Vázquez-Carrasco; Ana Olavarría-Jaraba; Emily Grott (SAGE Open)
Service Dominant Logic (SDL) proposes value creation as a process based on service, the success of which ultimately depends on employees’ service orientation. Given that universities are the nest of future employees, and the latest World Economic Forum Future of Jobs Report highlights skills such as empathy and active listening, leadership and social influence—all of which are reflected in service orientation – universities seem best placed to harness these skills. However, no previous studies have focused on how to develop service orientation through marketing courses in universities. A quasi-experimental approach using differences-in-differences design (DID) was conducted to test how service-learning contributes to service orientation in marketing courses. Data analyzed by using Structural Equation Modelling (SEM), indicates that individual service orientation can be fostered through a service-learning experience. Our findings suggest that service orientation is driven mainly by the social experience. Moreover, no significant effect of the academic learning of the marketing course on the service orientation was observed. Essentially, the study provides two main insights: the role of the university in value creation through the learning process, and the effects of designing training programs based on service-learning for future marketing personnel success.